Sosialisasi Koperasi Desa Sebagai Penggerak Ekonomi Masyarakat Desa Bottopenno Kabupaten Wajo - Akbar; Siardin Andi Djemma; Novianti; Nabila Batara Ugi (Compile Journal of Society Service, 2025)
Village co-operatives play a crucial role in the economic development of communities, particularly in rural areas, and are considered a key pillar of the national economy under Law UU RI No. 25 of 1992. This community service research aims to increase community understanding of co-operatives and to attract their interest in joining and contributing to the management of co-operatives in Bonttopenno Village, Wajo Regency. To achieve this goal, socialization was conducted using discussion and outreach methods as the most effective strategy. This community service has succeeded in providing a deeper understanding of the functions, benefits, and operational mechanisms of village cooperative units as drivers of the community economy.